Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1001/archpedi.159.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Combining Clinical Risk Factors With Serum Bilirubin Levels to Predict Hyperbilirubinemia in Newborns

Abstract: Clinical risk factors significantly improve prediction of subsequent hyperbilirubinemia compared with early TSB levels alone, especially in those with early TSB levels above the 75th percentile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 31 publications
4
57
2
2
Order By: Relevance
“…However, infants born at 38 weeks' gestation were categorized as low-risk infants, 29 possibly because of observations (n = 48 patients treated for hyperbilirubinemia) of no significant difference in rates of hyperbilirubinemia between infants born at 38 to 39 weeks and infants born at $40 weeks' gestation. 30 Our study confirms several smaller (n = 73-270 patients) US studies 12,[31][32][33] documenting an impact of each decreasing week of gestation on the risk of developing severe hyperbilirubinemia. Given that infants born not only after 37 but also after 38 weeks' gestation were, in most combinations of other perinatal risk factors, found to be at moderate to high risk for hyperbilirubinemia (Figure 1), we suggest that a GA of 38 weeks should be listed as a major risk factor in coming updates of neonatal hyperbilirubinemia guidelines.…”
Section: Discussionsupporting
confidence: 84%
“…However, infants born at 38 weeks' gestation were categorized as low-risk infants, 29 possibly because of observations (n = 48 patients treated for hyperbilirubinemia) of no significant difference in rates of hyperbilirubinemia between infants born at 38 to 39 weeks and infants born at $40 weeks' gestation. 30 Our study confirms several smaller (n = 73-270 patients) US studies 12,[31][32][33] documenting an impact of each decreasing week of gestation on the risk of developing severe hyperbilirubinemia. Given that infants born not only after 37 but also after 38 weeks' gestation were, in most combinations of other perinatal risk factors, found to be at moderate to high risk for hyperbilirubinemia (Figure 1), we suggest that a GA of 38 weeks should be listed as a major risk factor in coming updates of neonatal hyperbilirubinemia guidelines.…”
Section: Discussionsupporting
confidence: 84%
“…Comparison of the predischarge TSB risk zone to a slightly modified version of Newman's risk index (developed to predict a post-discharge TSB >20 mg dl À1 ) found that the discrimination of the TSB risk zone (c ¼ 0.79) was superior to the clinical risk factor score (c ¼ 0.69), and that neonates who subsequently develop hyperbilirubinemia have predischarge TSB values that are in higher percentiles. 19 In our study, discriminating abilities of TcB alone (c ¼ 0.72) and combined tool based on TcB and gestation at birth (c ¼ 0.75) were better than that of clinical risk factors alone (c ¼ 0.58). However, these values of c-statistics are lower than those reported by most of previous studies.…”
mentioning
confidence: 46%
“…Current literature reports that combining clinical risk factors with bilirubin levels can be useful in predicting later significant or severe hyperbilirubinemia. 29,30 The predischarge bilirubin level, expressed as a risk zone on the bilirubin nomogram and used alone or when combined with multiple clinical risk factors had similar accuracy for predicting significant hyperbilirubinemia. In one single-center study, an infant's gestational age improved the overall predictive accuracy of predischarge bilirubin risk zone.…”
Section: Screening Testsmentioning
confidence: 97%